Development of A System for the Production Process Monitoring Using Telegram Bot - Yevsieiev, V.; Maksymova, S.; Starikova, S. (European Scientific Platform, 2022)
Modern trends in the production development within the Industry 4.0 concept framework the are based on the introduction of new information technologies into existing production processes. One of the biggest challenges in implementing Industry 4.0 is to upgrade existing production lines to improve process monitoring systems, which consequently improves quality and cost-effectiveness by predicting production progress.
Keywords: Industry 4.0; monitoring systems; Telegram API.